Assessing Materials Management Practices Effect on Firm's Performance in Ghana Using Dominance Analysis: Evidence from a Listed Company. Issue 2 (December 2021) - Essel, Ronald Ebenezer
The objective of this study is to empirically examine the effect of materials management on a firm's performance by exploring employee views and utilizing a firm's financial statement data within the Ghanaian context, focusing on Fan Milk Limited, a listed manufacturing firm in Ghana. A cross-sectional research design was espoused for the study, utilizing questionnaires completed by 240 respondents selected via simple random sampling. SPSS version 25.0 was utilized for data analysis, which included descriptive statistics, principal component analysis, exploratory factor analysis with varimax rotation, reliability/validity analysis, and multivariate regression aided with relative importance analysis via dominance analysis. The study found significant positive relationships between all eight materials management practices and a firm's performance. Dominance analysis further revealed that materials requirement planning and control was the most important predictor of a firm's performance, while ergonomics was the least important predictor of performance. Managerial recommendations established should be viewed critically while managing manufacturing firms.